Synthesis, microstructure, multifunctional properties of mayenite Ca12Al14O33 (C12A7) cement and graphene oxide (GO) composites - Chaval Sriwong; Chaiwat Phrompet; Wattana Tuichai; Attaphol Karaphun; Ken Kurosaki; Chesta Ruttanapun (My University, 2020)
Abstract The Pristine Mayenite Ca 12 Al 14 O 33 (C12A7) Cement was simply synthesized by using solid-state reaction. The C12A7 and Graphene Oxide (GO) composites (C12A7_GO-x) with various contents of the GO suspension loading (x = 0 wt%, 1 wt%, 2 wt%, 3 wt%, and 4 wt%) were directly prepared by mixing the C12A7 and GO. X-ray diffraction results of pristine C12A7 and all C12A7_GO composites indicated a pure phase corresponding to the standard of C12A7 cement. Raman spectroscopy confirmed the existence of GO in all C12A7_GO samples. Scanning Electron Microscopy (SEM) showed the micrometer grain sizes and the occurrence of grain boundary interfaces for GO incorporation in all C12A7_GO samples. UV–Vis spectroscopy revealed the absorption value of all C12A7_GO samples and red shift near longer wavelengths when increasing the GO concentrations. The dielectric constant of C12A7_GO composites can be explained by the high density of free electron charges for the interfacial polarization on the GO surface. The maximum specific capacitance of C12A7_GO-4 electrode of 21.514 at a current density of 0.2 A g −1 can be attributed to the increase in the electrochemically active surface area for the formation of the electrical double layer capacitors behavior and the effects of high surface area GO connections. Also, the mechanical properties exhibited an increase in Vickers indenter hardness ( HV ) values with increasing GO contents. The highest HV value was 117.8 H V/2 kg at the C12A7_GO-4 sample. These results showed that the composite materials of the pristine C12A7 cement with GO were highly efficient. All in all, the GO material contained a high potential for enhancing low-cost cement materials in multifunctional properties such as optical, dielectric, electrochemical, and mechanical properties.
Keywords: Ammonia Synthesis and Nitrogen Reduction